The Future of Publications in the Humanities: From the Perspective of Evaluation - Žic Fuchs, Milena; Stojanovski, Jadranka (2009)
The paper discusses possible impacts of bibliometric evaluation on the future of publications in the Humanities. Various evaluation systems (the Norwegian model, the Australian model etc.) are discussed from the point of view of the specific nature of Humanities research seen through the optics of publication of articles and books in national languages. Special stress is placed on the importance of monographs and chapters in monographs, as well as the necessity of including collections such as revised editions. Attempts at bibliometric evaluation in Humanities disciplines could result in changes of publication culture in the future and for this reason it is very important that any such attempts cover the diverse types of publications as well as output in national languages. A comparison is also made with the hard sciences.
ENG